Decision Support System to Determine the Amount of Performance Allowances Using the Simple Additive Weighting (SAW) Method at the Karo District Social Service - Lamtiur Pasaribu; Fristy Riandari (Institute of Computer Science (IOCS), 2020)
This study was made to determine the amount of employee performance allowances in accordance with their performance achievements. The method used is simple additive weighting (SAW). Decision support systems are generally defined as a system that is capable of producing solutions and handling problems. Decision support systems are not intended to replace the role of decision makers, but to assist and support decision makers. The method used in the decision-making process is Simple Additive Weighting (SAW), the process of the Simple Additive Weighting method, which is looking for the weighted sum of the performance ratings for each alternative on all criteria, making a table of the suitability rating of each alternative on each criterion and making a decision matrix. There are four criteria used in the selection using the SAW method, namely attendance, performance, responsibility and teamwork. The method and design used in making this application use Sublime Text and also the database server as a programming language and also use PHP and MySQL programming. The system is designed based on website